Growing self-estemm and discovering intelligences through oral production (2002)
After having applied a needs analysis in an eleventh grade course of English, I could notice that there was a big lack of security and self-confidence in the students. They expressed in different data-gathering instruments their fear when speaking in front of the class. Also, they talked about their insecurity when pronouncing English and the need for more opportunities for developing speaking. Therefore, the implementation of an innovation in class was carried out in order to respond to the students¿ needs and make them discover their talents. The implementation was successful and students improved some areas of their communicative competence.